Dressed Coolie Woman. All Gold. Trinidad B.W.I. - (:unkn) unknown (My University, 2008)
East Indian woman in traditional wear, adorned with gold jewelry.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; Jewelry--India; Clothing and dress--Trinidad and Tobago